2017
DOI: 10.1038/s41598-017-13191-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep-level defects in n-type GaAsBi alloys grown by molecular beam epitaxy at low temperature and their influence on optical properties

Abstract: Deep-level defects in n-type GaAs1−xBix having 0 ≤ x ≤ 0.023 grown on GaAs by molecular beam epitaxy at substrate temperature of 378 °C have been injvestigated by deep level transient spectroscopy. The optical properties of the layers have been studied by contactless electroreflectance and photoluminescence. We find that incorporating Bi suppresses the formation of GaAs-like electron traps, thus reducing the total trap concentration in dilute GaAsBi layers by over two orders of magnitude compared to GaAs grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 46 publications
10
33
0
Order By: Relevance
“…However, given that there was little evidence of bismuth incorporation from XRD, the origin of the long wavelength emission is uncertain in this sample. It may be caused by various reasons including possible localised states with strong PL signal at longer wavelengths at low temperature [5] and/or recombination via defect related traps [19] caused by the low growth temperature. We make a note of caution here that such long-wavelength emission bands may also relate to the low-temperature grown InGaAs layer of the cap as we recently observed in This is the author's peer reviewed, accepted manuscript.…”
Section: Ingaasbi Samples and Preliminary Characterisation Using Xrd mentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that there was little evidence of bismuth incorporation from XRD, the origin of the long wavelength emission is uncertain in this sample. It may be caused by various reasons including possible localised states with strong PL signal at longer wavelengths at low temperature [5] and/or recombination via defect related traps [19] caused by the low growth temperature. We make a note of caution here that such long-wavelength emission bands may also relate to the low-temperature grown InGaAs layer of the cap as we recently observed in This is the author's peer reviewed, accepted manuscript.…”
Section: Ingaasbi Samples and Preliminary Characterisation Using Xrd mentioning
confidence: 99%
“…This sample exhibited very strong broad low temperature PL in spectral range 1750-2800nm, which indicated the presence of localised states. We cannot rule out the possibility of recombination via defect related traps either in InGaAsBi layer itself [19] or This is the author's peer reviewed, accepted manuscript. However, the online version of record will be different from this version once it has been copyedited and typeset.…”
Section: Rutherford Back Scattering Measurementsmentioning
confidence: 99%
“…Low temperatures needed to incorporate larger concentrations of Bi make molecular-beam epitaxy (MBE) the preferred method of synthesis, although progress has been made using metal-organic vapour phase-epitaxy [15][16][17]. GaAsBi alloys still show surprisingly high photoluminescence (PL) intensity for these low growth temperatures, which is attributed to the Bi surfactant effect and reduced density of As-related point defects that typically form in low-temperature GaAs [18,19]. In the picture of the valence band (VB) anti-crossing, incorporated individual Bi atoms produce a resonant state below the extended GaAs VB causing the optical band gap reduction [2,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GaSbBi alloys have not been explored much, in contrast to GaAsBi alloys, which have been extensively studied in recent years by several groups. [14][15][16][17][18][19][20][21][22][23][24] In the case of GaAsBi, it is observed that Bi tends to segregate toward the surface and to form droplets due to its large size in comparison with arsenic. Therefore, the growth of III-V-Bi materials is usually achieved using very-low growth temperatures and a near stoichiometric V/III ratio.…”
mentioning
confidence: 99%
“…Such conditions usually favor the formation of point defects, which are sources of deep levels and nonradiative recombination in this material system. 24 Compared to GaAsBi, the situation in GaSbBi can be different due to the smaller difference between the group V atoms in terms of their electronegativities and sizes. As shown in Ref.…”
mentioning
confidence: 99%